2018
DOI: 10.1007/s10661-018-6894-x
|View full text |Cite
|
Sign up to set email alerts
|

The potato tuber content of microelements as affected by organic fertilisation and production system

Abstract: The objective of the work was to determine the effect of undersown catch crops, which were either autumn-incorporated or left on the soil surface as mulch for spring incorporation, on the microelement content in the tubers of potato cultivated in the integrated and organic production system. Field research was conducted at the Zawady Experimental Farm owned by Siedlce University of Natural Sciences and Humanities, Poland (52° 03′ 39″ N, 22° 33′ 80″ E). The following two factors were examined in the study: (i) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(45 reference statements)
2
3
0
Order By: Relevance
“…The zinc concentration varied from 9.8 to 26.0 mg/kg of DW, matching with previous results of fertilized and organic Zn concentrations [ 5 , 31 , 32 ]. The concentrations did not vary depending on the flesh coloration of the tuber, but the purple sweet potato tuber had a significantly lower Zn concentration of only 8.2 mg/kg of DW.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The zinc concentration varied from 9.8 to 26.0 mg/kg of DW, matching with previous results of fertilized and organic Zn concentrations [ 5 , 31 , 32 ]. The concentrations did not vary depending on the flesh coloration of the tuber, but the purple sweet potato tuber had a significantly lower Zn concentration of only 8.2 mg/kg of DW.…”
Section: Resultssupporting
confidence: 88%
“…In general, higher magnesium levels were detected in the tubers of cross-breeds of Blue Congo and Granola. The overall levels varied from 629 to 1264 mg/kg of DW with an average of 1015 mg/kg of DW, which is comparable to both conventional and organically cultivated potato tubers, that averaged from 1183 to 1646 mg/kg of DW [ 5 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mean iron content of potato tubers in Acco is significantly ( P < .01) higher than that in Huancayo. This could be due to the high iron content of the soils of Acco, coinciding with expectations that the availability of iron and zinc is greater with lower pH and higher organic matter content of soils (Gąsiorowska, Plaza, Rzążewska, Cybulska, & Górski, 2018; Lindsay, 1991; Rengel, 2015).…”
Section: Resultssupporting
confidence: 71%
“…The concentrations of mineral elements and DM in potato tubers and tuber size are influenced by environmental, developmental, and management practices, which can interact with each other and with genetic factors. (Gąsiorowska et al., 2018; Kromann et al., 2016; White et al., 2012). While further research is needed to better understand relationships between these characteristics, experiments with the application of mineral fertilizers by White et al.…”
Section: Discussionmentioning
confidence: 99%
“…In Poland, in a recent study conducted by Wierzbowska et al [38], organically grown potatoes had a higher content of B (8.6-8.9 mg kg −1 ) and Cu (2.8-3.1 mg kg −1 ), and a lower content of Fe (47.0-47.1 mg kg −1 ), Mn (6.0-6.4 mg kg −1 ), and Zn (11.9-12.2 mg kg −1 ) than potatoes grown in conventional systems. Gąsiorowska et al [39] reported that potatoes cultivated in the integrated production system contained more Cu, Mg, and Zn, whereas organic tubers had more Fe and B.…”
Section: Farming Systems Cultivarsmentioning
confidence: 99%